2002
DOI: 10.1046/j.1464-5491.2002.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

eNOS4 polymorphism of the endothelial nitric oxide synthase predicts risk for severe diabetic retinopathy

Abstract: We demonstrate in Caucasians with Type 1 diabetes that (i) eNOS4a/a is associated with absent or non-severe DR, and (ii) eNOS4b/b is associated with severe DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 29 publications
(42 reference statements)
2
30
2
6
Order By: Relevance
“…Some studies (9,10), but not all (11,12), reported that the "a" allele of the eNOS 27-bp repeat polymorphism was positively associated with DN. In contrast, Taverna et al (13) reported that the "b" allele and the bb genotype were associated with severe DR. Similarly, Frost et al (14) reported that the bb genotype of the 27-bp repeat was associated with DR.…”
Section: Enos Gene and Diabetic Macular Edemamentioning
confidence: 91%
See 1 more Smart Citation
“…Some studies (9,10), but not all (11,12), reported that the "a" allele of the eNOS 27-bp repeat polymorphism was positively associated with DN. In contrast, Taverna et al (13) reported that the "b" allele and the bb genotype were associated with severe DR. Similarly, Frost et al (14) reported that the bb genotype of the 27-bp repeat was associated with DR.…”
Section: Enos Gene and Diabetic Macular Edemamentioning
confidence: 91%
“…Recently, the 27-bp repeat has been found to be associated with the progression of diabetic nephropathy (DN) (9) or advanced DN (10), although some studies did not confirm this association (11,12). Also, the possible association of eNOS polymorphisms with DR has been examined in several studies, and a "b" allele of the 27-bp repeat was associated with a high risk of DR in type 1 diabetes (13,14). In the present study, we examined the eNOS polymorphisms to assess their possible association with DR and maculopathy.…”
mentioning
confidence: 99%
“…36 Higher total plasma insulin concentration has been reported, [37][38][39] which seems to be genetically predetermined 40 and which is a risk factor for retinopathy. Other reasons may include increased vitamin D deficiency in Asians 41 which has been shown to affect diabetic retinopathy, 42 earlier changes required in treatment in Asians 37 which is considered a risk factor, 43 and heath care access which will invariably affect control, diagnosis, and progression and eventually make an impact on diabetic retinopathy. Precisely how these different risk factors influence diabetic retinopathy in the two races is largely undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Bazı çalışmalarda VEGFün 5' kodlanmamış bölgesinde C-634G olarak tanımlanan genel bir polimorfizmin diabetik retinopati mevcudiyeti ile doğrudan ilişkili olduğu ve fonksiyonel olarak önemli olduğu sonucuna varılmıştır. eNOS geninde çeşitli polimorfizmler tanımlanmıştır (14)(15).Tip I DM' da 27-bp tekrarının 'b' alleli yüksek diabetik retinopati riski ile ilişkili bulunmuştur (16,17). (32).…”
Section: Nitrik Oksitin Gen Haritasındaki Lokusu : 7q36unclassified
“…Özellikle promotor bölgesindeki T-786C, 4. intron bölgesinde 27-bp tekrarı ve 7. eksondaki Glu298Asp dikkat çekmiştir. Tip I DM'da 27-bp tekrarının 'b' aleli yüksek diabetik retinopati riski ile ilişkili bulunmuştur (16,17). Tip II DM'lu hasta grubunda eNOS gen polimorfizmi (T-786C, promotor bölgede ve intron 4 deki 27bp tekrarı) makula ödeminin oluşumu ile direkt ilişkili bulunmuştur.…”
Section: Introductionunclassified